Soy crisps incorporated with red seaweed, Kappaphycus alvarezii - Lim, Cheak Ting; Patricia Matanjun (Hibiscus publisher, 2024)
Kappaphycus alvarezii (KA), an underutilized seaweed with potential benefits, is particularly used to extract kappa-carrageenan in the food industry. There is a notable absence of commercially available snacks that incorporate KA. This study aimed to develop soy crisps incorporating different concentrations of KA powder (0%, 2.5%, 5%, 7.5%, and 10%) and to determine the best formulation for addressing the gap. KA-incorporated crisps showed darker colour with more redness and yellowness and ideal texture. The crisps with 5% KA (F3) received significantly highest sensory scores for texture, taste, and overall acceptance (p<0.05). F3 crisps had higher ash, protein, fibre, and carbohydrates, and lower fat compared to control (F1), while providing more energy. In conclusion, these findings highlight the potential of KA-incorporated crisps as a nutritious and palatable snack option.